(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the haemodynamic changes between Laryngeal Mask Airway (LMA) insertion & Endotracheal intubation in day care surgery. Study Design: Quasi Experimental Study. Place and Duration of Study: This study was conducted at the Department of Anaesthesia, Divisional Headquarter Teaching Hospital Mirpur from May 2015 to May 2016. Materials and Methods: This study was conducted after taking permission from the Hospital Ethical Committee. One hundred patients fulfilling inclusion criteria were selected by non probability convenient sampling after taking informed written consent. They were divided into two groups (LMA-A and ETT- B) scheduled for different elective day care surgical procedures under general anaesthesia. Group A comprised of fifty patients in whom LMA was inserted. Group B comprised of fifty patients in whom ETT was inserted. Patient , s systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), heart rate (HR) and pulse oximetry (SPO2) baseline and on 01,03,05,07,09 than after every three minutes were recorded. All the data compared and analyzed by SPSS-10. Results: It was observed that 99% i.e. forty-eight patients of group A (n=50) did not show intraoperative hemodynamic changes and only 1% i.e.2 patients showed hemodynamic changes. While 95% i.e. forty patients of group B (n=50) did not show hemodynamic changes and remaining only 5% i.e. 10 patients showed intraoperative hemodynamic changes. Conclusion: The use of LMA significantly reduces the intaoperative hemodynamic changes compared to ETT in day care surgery.